On some ways to implement state-multiplicative fault detection in discrete-time linear systems - Krokavec, Dušan; Filasová, Anna (Zielona Góra: Uniwersytet Zielonogórski)
New design conditions on the observer based residual filter design for the linear discrete-time linear systems with zoned system parameter faults are presented. With respect to time evolution of residual signals and with a guarantee of their robustness, the design task is stated in terms of linear matrix inequalities, while the recursive implementation of algorithms is motivated by the platform existence for real-time processing. A major objective is to analyze the configuration required and, in particular, a new characterization of the norm boundaries of the multiplicative zonal parametric faults to be projected onto the structure of the set of linear matrix inequalities.
Keywords: linear discrete-time systems; state-multiplicative faults; Luenberger observers; residual filters; linear matrix inequalities